Wintering heifer calve that are to be fattened for the summer or early fall market. - Smith, E.F.; Good, D.L.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
This is a report of the wintering phase of the third of a series of tests started in the fall of 1947 to develop a system or systems of fattening heifer calves similar to the deferred full feeding system involving the use of good quality steer calves which was developed at Kansas State College. The objective of this experiment are: (1) To develop a system of deferred full feeding using heifer calves (2) To compare different wintering rations for heifer calves. (3) To compare various methods of finishing heifers.
Keywords: Beef; Heifers; Gain; Protein